Fruit growth and fruit drop in banana passion fruit plants (Passiflora tripartita var. mollissima) (2018)
Growth is an irreversible increase in the size of plant organs that may involve changes in their form, and is accompanied by processes such as morphogenesis and cell differentiation.  The mathematical expression of fruit growth in cultivated plants allows one to estimate aspects related to production, and contributes to defining protocols applicable to the agronomic management of the crop.  A field trial was carried out in Caldas (Boyaca, Colombia), to describe the dynamics of different variables involved in the growth and fall of fruits in Banana passion fruit plants (Passiflora tripartita var. mollissima).  Mathematical models were developed for variables commonly used to describe fruit growth.  The evaluated variables presented values of R2 higher than 0.98, except for the absolute growth rate of fruit length and at the time of fruit drop, whose R2 values were 0.82 and 0.76, respectively. The results showed that the relative growth rate presented maximum values up to 22 days after floral opening, whereas the absolute growth rate presented the highest value between 15-22 days after floral opening.  The length and width of the fruits showed a sigmoid-shaped curve, typical of other previously reported Passifloraceae. The maximum fruit fall occurred at 15 days after the floral opening and it was found that only 38.9% of the flowers develop fruits that reach the time of harvest. This information contributes to the technical management and optimal production of banana passion fruit.